In pursuit of a better tool bag. Issue 1 (23rd April 2018) - Skipworth, Stan
Abstract : Recently, I found myself in the uneasy position of trying to complete a home repair inspite of my being completely ill‐equipped to do the job. In addition to having no tools that were truly essential for the task, I also had no ladder capable of reaching the area, nor the experience to properly deal with the problem in a manner that would make a lasting difference.